The Effect of Product Quality and E-Servicescape on Customer Loyalty in Secondhands MSMEs Moderated by Trust - Kustiadi Basuki; Khairani Putri Yuniarta (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of this research product quality and e-servicescape on customer loyalty moderated by trust (Trust). The population in this study were 191 Second Hands MSME customers and prospective customers, with samples using structural equation model (SEMstatistical test tools partial least squares (PLS) through SmartPLS software. Data collected by questionnaires that have been tested for validity and reliability. The results of this study are from the first hypothesis, it was found that the relationship between Product Quality and Customer Loyalty is a positive or significant effect on SMEs Second Hands. The results of the second hypothesis tester, it was found that the relationship between E-Servicescape and Customer Loyalty had a positive or significant effect on Secondhands MSMEs. The results of the third hypothesis, it is found that the relationship of Trust (Trust) to Customer Loyalty has a positive or significant effect on Second Hands SMEs. The results of the fourth hypothesis, it is found that Product Quality on Customer Loyalty cannot be moderated by Trust (Trust positively and significantly in Secondhands MSMEs. The results of the fifth hypothesis show that E-Servicescape on Customer Loyalty cannot be moderated by Trust) positive and significant on Second Hands SMEs.